1995
DOI: 10.1128/jb.177.2.336-342.1995
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus haemolyticus contains two D-glutamic acid biosynthetic activities, a glutamate racemase and a D-amino acid transaminase

Abstract: Two D-glutamic acid biosynthetic activities, glutamate racemase and D-amino acid transaminase, have been described previously for bacteria. To date, no bacterial species has been reported to possess both activities. Genetic complementation studies using Escherichia coli WM335, a D-glutamic acid auxotroph, and cloned chromosomal DNA fragments from Staphylococcus haemolyticus revealed two distinct DNA fragments containing open reading frames which, when present, allowed growth on medium without exogenous D-gluta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
47
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 26 publications
0
47
0
Order By: Relevance
“…YM-1 and perhaps Staphylococcus aureus have both dat and the racemase gene that can functionally complement the D-glutamate-requirement of an E. coli murI mutant. However, whether both genes are required for D-glutamate synthesis by host cells remains unknown (Fotheringham et al, 1998;Pucci et al, 1995). B. subtilis has yheM, which encodes a putative D-amino acid aminotransferase that is similar (65 % amino acid sequence similarity) to S. haemolyticus Dat aminotransferase (Kunst et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…YM-1 and perhaps Staphylococcus aureus have both dat and the racemase gene that can functionally complement the D-glutamate-requirement of an E. coli murI mutant. However, whether both genes are required for D-glutamate synthesis by host cells remains unknown (Fotheringham et al, 1998;Pucci et al, 1995). B. subtilis has yheM, which encodes a putative D-amino acid aminotransferase that is similar (65 % amino acid sequence similarity) to S. haemolyticus Dat aminotransferase (Kunst et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in addition to its proposed role in cell wall biosynthesis, glutamate racemase is also predicted to be the major source of D-glutamate for PDGA capsule synthesis in B. anthracis (9). In contrast to most bacteria that possess only one glutamate racemase gene (5,10,14,18,19,26,29,33,35,40,61), the B. anthracis genome contains two genes (BAS0806 and BAS4379) predicted to encode glutamate racemases, which are designated racE1 and racE2. Recently, inactivation of racE2 was reported to cause a severe growth defect in B. anthracis, while inactivation of racE1 only moderately inhibited growth (52).…”
mentioning
confidence: 99%
“…5.1.1.3), which catalyzes the reversible stereoinversion of L-glutamate (5,14,31). Insights into the cofactor-independent amino acid racemases have begun to emerge from biochemical studies of enzymes isolated from several organisms, including Bacillus subtilis, Bacillus pumilus, Bacillus sphaericus, Escherichia coli, Lactobacillus fermentum, Lactobacillus brevis, Aquifex pyrophilus, Staphylococcus haemolyticus, Brevibacterium lactofermentum, and Mycobacterium tuberculosis (1,2,5,10,14,18,19,21,28,29,33,35,40,47,58,61), as well as the recently described crystal structure of RacE-D-glutamate from B. subtilis (43). Several studies have identified glutamate racemase as an essential gene in B. subtilis and E. coli, which has led to the prediction that glutamate racemase activity is important for peptidoglycan biosynthesis in these organisms (14,31).…”
mentioning
confidence: 99%
“…D-AAT activity is found in various gram-positive bacteria, including Bacillus (8,28,29), Staphylococcus (22), and Listeria (31), and yet recent biotechnology studies have mainly focused on thermophilic or mesophilic Bacillus enzymes due to their high catalytic activity and broad substrate specificity (4,9,10,23). For example, the D-AAT from thermophilic Bacillus sp.…”
mentioning
confidence: 99%